Penguatan peran pembinaan Taman Bacaan Masyarakat (TBM) Darussalam untuk mendukung program makanan bergizi dan sehat di Kampung Darussalam Kecamatan Sei Lapan Kabupaten Langkat - Yusnadi; Anugrah Setiawan; Sani Susanti; Jubaidah Hasibuan; Khodijah Tussolihat Dalimunthe; Radini (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to strengthen the role of the Darussalam Community Reading Garden (TBM) in supporting initiatives to provide nutritious and healthy food in Darussalam Village, Sei Lepan District, Langkat Regency. Activities are implemented through nutrition literacy training, the development of healthy food education modules, and the formation of family nutrition support groups based on TBM management. The implementation method uses a participatory approach, involving TBM managers, PKK cadres, and the local community. The program results show a significant increase in nutritional understanding among participating homemakers, improved skills in managing local food ingredients, and a strengthening of the TBM's role as a community nutrition education center. This program has the potential to be replicated in other areas as a model for integrating literacy and community-based health